Novel GATA6-FOXO1 fusions in a subset of epithelioid hemangioma - Antonescu, Cristina R.; Huang, Shiqiang; Sung, Yun-Shao; Zhang, Lei; Helmke, Burkhard Maria; Kirchner, Martina; Stenzinger, Albrecht; Mechtersheimer, Gunhild (Modern pathology, 2021)
The genetic hallmark of epithelioid hemangioma (EH) is the presence of recurrent gene fusions involving FOS and FOSB transcription factors, which occur in one-third of the cases. Certain clinical, pathologic, and genotypic correlations have been described, with FOS-related fusions being more often detected in skeletal and cellular variants of EH, while FOSB gene rearrangements are more commonly associated with atypical histologic features and penile location. These fusions are infrequently detected in the cutaneous or head and neck EH. Overall, two-thirds of EH lack these canonical fusions and remain difficult to classify, especially when associated with atypical features and/or clinical presentations. Triggered by an index case of an intravascular soft tissue EH with a novel GATA6-FOXO1 gene fusion by targeted RNA sequencing (Archer® FusionPlex® Sarcoma Panel), we have investigated 27 additional EH cases negative for FOS and FOSB gene rearrangements for this novel abnormality to determine its recurrent potential, and its association with clinical and pathologic features. Four additional EH cases were found to display GATA6-FOXO1 fusions (18%). There were three females and two males, with a mean age of 32 years old. Three lesions occurred in the head and neck (dura, nasopharyngeal, and cheek), one in the back and one in the leg. Two of these lesions were cutaneous and one was intravascular in the subcutis of the leg. Microscopically, the tumors showed a variegated morphology, with alternating vasoformative and solid components, extravasated red blood cells and mild to moderate cytologic atypia. None showed brisk mitotic activity or necrosis. Tumors were negative for FOS and FOSB by immunohistochemistry. In conclusion, we report a new GATA6-FOXO1 fusion in a subset of EH, with a predilection for skin, and head and neck location. The relationship of this novel molecular subset with the more common FOS/FOSB fusion-positive EH remains to be determined.
Online veröffentlicht: 14. Dezember 2020
Gesehen am 10.11.2023